2016
DOI: 10.1186/s12645-016-0023-8
|View full text |Cite
|
Sign up to set email alerts
|

Profiling lung adenocarcinoma by liquid biopsy: can one size fit all?

Abstract: BackgroundCancer is first and foremost a disease of the genome. Specific genetic signatures within a tumour are prognostic of disease outcome, reflect subclonal architecture and intratumour heterogeneity, inform treatment choices and predict the emergence of resistance to targeted therapies. Minimally invasive liquid biopsies can give temporal resolution to a tumour’s genetic profile and allow the monitoring of treatment response through levels of circulating tumour DNA (ctDNA). However, the detection of ctDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…It is an EGFR protein kinase inhibitor designated to treat patients with NSCLC by deleting the 19 number exon. Li and colleagues also used another drug to treat metastasized renal carcinoma named sorafenib [140,143].…”
Section: Machine Learning In Oncologymentioning
confidence: 99%
“…It is an EGFR protein kinase inhibitor designated to treat patients with NSCLC by deleting the 19 number exon. Li and colleagues also used another drug to treat metastasized renal carcinoma named sorafenib [140,143].…”
Section: Machine Learning In Oncologymentioning
confidence: 99%
“…In one such case study, Li and colleagues built drug sensitivity models from cancer cell lines treated with erlotinib [an EGFR protein kinase inhibitor approved for NSCLC patients with activating mutations: exon 19 deletion (del19) or exon 21 (L858R) substitution] and sorafenib (a non-specific kinase inhibitor approved for advanced renal cell carcinoma) [48,51]. Models were then used to stratify patients in the BATTLE (Biomarker-integrated Approaches of Targeted Therapy for Lung Cancer Elimination) clinical trial [48,52], with identified biomarkers backwards justified with knowledge of the mechanism of action of each kinase inhibitor drug.…”
Section: Predictive Biomarkers For Personalised Cancer Carementioning
confidence: 99%
“…These identified mutation genes or pathways might be drivers contributing to cancer (Youn and Simon, 2011; Dees et al, 2012; Hua et al, 2013; Merid et al, 2014; Leiserson et al, 2015) or potential diagnosis biomarkers for a cancer (Ece Solmaz et al, 2015; Clifford et al, 2016; Li et al, 2016; Sato et al, 2016). For example, Clifford et al identified a panel of 400 mutations covering more than 80% of the lung adenocarcinoma (LUAD) patients from The Cancer Genome Atlas (TCGA) database (Clifford et al, 2016). However, in an independent validation dataset, this panel of mutations only covered 55% of 183 patients (Clifford et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Clifford et al identified a panel of 400 mutations covering more than 80% of the lung adenocarcinoma (LUAD) patients from The Cancer Genome Atlas (TCGA) database (Clifford et al, 2016). However, in an independent validation dataset, this panel of mutations only covered 55% of 183 patients (Clifford et al, 2016). It is not surprising that the coverage drops so much in the validation dataset because the distribution of somatic mutations is highly heterogeneous (N.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation